2021
DOI: 10.3390/children8121144
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lesson for Respiratory Syncytial Virus (RSV): Hygiene Works

Abstract: Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections (LRTIs) in infants worldwide. The global direct medical cost associated with RSV LRTIs reaches billions of dollars, with the highest burden in low–middle-income countries. Many efforts have been devoted to improving its prevention and management, including both non-pharmaceutical and pharmaceutical strategies, often with limited routine use in high-income countries due to high costs. During the ongoing COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…NPI cannot reasonably be applied throughout childhood and throughout the period of intense RSV circulation; however, behavioural changes among household contacts of newborns and young infants (i.e. increased hand washing, covering the mouth when coughing, and avoidance of large gatherings and close contact with sick people) are likely to assist in decreasing the incidence of infection in infants aged 3 months or younger [ 25 , 27 ] and, therefore, ongoing promotion of these measures is recommended [ 25 , 36 ].…”
Section: Epidemiology and The Impact Of Non-pharmaceutical Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…NPI cannot reasonably be applied throughout childhood and throughout the period of intense RSV circulation; however, behavioural changes among household contacts of newborns and young infants (i.e. increased hand washing, covering the mouth when coughing, and avoidance of large gatherings and close contact with sick people) are likely to assist in decreasing the incidence of infection in infants aged 3 months or younger [ 25 , 27 ] and, therefore, ongoing promotion of these measures is recommended [ 25 , 36 ].…”
Section: Epidemiology and The Impact Of Non-pharmaceutical Interventionsmentioning
confidence: 99%
“…During the first 2 years of the COVID-19 pandemic, the benefits of non-pharmaceutical measures on RSV infection in infants have been obvious, although temporary, since the benefits were suspended when the restrictions were lifted [ 25 ]. Now, the impetus should be to prevent the onset of pandemic restriction “fatigue” and encourage people to maintain certain long-term non-pharmaceutical hygiene measures.…”
Section: Management Options For Prevention: a Public Health Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Human RSV is associated with a substantial burden of disease in children and elders [ 7 , 10 , 35 , 38 , 42 , 50 , 51 ]. NPI, due to the SARS-CoV-2 pandemic, have led to the substantial disappearance of the conventional seasonal trend for RSV infections [ 1 , 24 , 29 , 30 , 31 , 52 , 53 , 54 , 55 , 56 , 57 ], that have been in turn followed by an unprecedented surge in incident cases [ 29 , 30 , 31 , 52 , 58 , 59 ]. Accurate statistics are unavailable, but GPs and pediatricians usually manage up to 97% of yearly incident cases as outpatients [ 16 , 60 , 61 ], representing a substantial burden for primary practitioners still struggling with the requirements of the SARS-CoV-2 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have suggested that viral mitigation measures such as masking may be an effective approach for managing asthma and COPD going forward based on the dramatic reductions in disease exacerbations during lockdown. 1,19 However, our data would suggest caution in applying viral mitigation strategies to young children with asthma because withdrawal of these measures led to an overcorrection in viral positivity and asthma cases. Such an overcorrection is biologically plausible because young children are immunologically naive.…”
Section: Resultsmentioning
confidence: 86%